Instructional Strategies Employed by Elementary Teachers in Strengthening Pupils’ Engagement and Academic Performance in Inclusive Classrooms - Mangila, Julius; Mangila, Benjamin (Jurnal Pendidikan Progresif, 2022)
Instructional Strategies Employed by Elementary Teachers in Strengthening Pupils’ Engagement and Academic Performance in Inclusive Classrooms. Objectives: This quantitative study ascertained Filipino teachers’ instructional strategies and pupils’ engagement and academic performance in select Philippine elementary schools. Methods: It employed the descriptive survey method, with questionnaire as data collection tool, and descriptive and inferential statistics as statistical tools. Findings: Results disclosed that “Classroom Management,” “Peer Support,” and “Individualized Education Plan” were the teachers’ leading instructional strategies while all instructional strategies were assessed as “Effective.” Pupils’ engagement was “High” while their performance in English, Mathematics, and Science subjects was “Fair.” Furthermore, teachers and pupils’ perceptions on the effectiveness of instructional strategies and their assessments on pupils’ engagement did not significantly differ. Conclusion: Teachers must employ varied instructional strategies to help learners effectively learn and to ensure that classrooms are inclusive to make them a more conducive place for teaching and learning.  Keywords: instructional strategies, pupils’ engagement, and academic performanceDOI: http://dx.doi.org/10.23960/jpp.v12.i2.202211